MODEL OF COMMUNICATIVE ENGLISH SYLLABUS FOR STUDENTS OF HOTEL DEPARTMENT AT SMK N 7 BENGKULU - Ayu Anisa Sartika; Hilda Puspita; Imranuddin . (Universitas Bengkulu, 2018)
This study was designed as a developmental research which was aimed at designing communicative English syllabus for students of Hotel Department at SMK N 7 Bengkulu. The researcher used needs analysis to find out the students’ needs of English. The instrument used was a set questionnaire items to collect the data. The population of this study was students and English teachers at SMK N 7 Bengkulu and hotel staff of Nala Seaside Hotel Bengkulu as well. The samples of this study were selected with two techniques sampling. The first technique sampling was random sampling for 80 students. The second technique sampling was total sampling for 3 English teachers and 12 hotel staff. The result of the study showed that listening skill gained 94%, speaking skill gained 91%, reading skill gained 74%, and writing skill gained 68%. From the result of data analysis, a syllabus was designed based on communicative approach and it had been tried out for three times.